2022
DOI: 10.1186/s10195-021-00621-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ulna shortening osteotomy: a cohort analysis of 106 patients

Abstract: Background Ulna shortening osteotomy (USO) for ulnar impaction syndrome (UIS) aims to improve pain and function by unloading the ulnar carpus. Previous studies often lack validated patient-reported outcomes or have small sample sizes. The primary objective of this study was to investigate patient-reported pain and hand function at 12 months after USO for UIS. Secondary objectives were to investigate the active range of motion, grip strength, complications, and whether outcomes differed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…We reviewed electronic patient records to confirm that the USO was performed for UIS, as USO may also be used for other indications. As in our previous study, 12 at least one of the following criteria needed to be met to be included in the study: 1) the surgeons explicitly diagnosed the patients with UIS in the electronic patient records; 2) wrist arthroscopy showed signs of type 2 lesions, such as triangular fibrocartilage complex (TFCC) degeneration and lunate chondropathy, according to Palmer; 19 3) magnetic resonance imaging (MRI) showed signs of focal abnormal signal intensity in the lunate, triquetrum, and ulnar head; 20 and 4) there was evident static or dynamic ulnar positive variance on standard posterior-anterior wrist radiographs in a neutral position. 21 This definition excluded three patients that underwent USO for other indications.…”
Section: Methodssupporting
confidence: 66%
See 3 more Smart Citations
“…We reviewed electronic patient records to confirm that the USO was performed for UIS, as USO may also be used for other indications. As in our previous study, 12 at least one of the following criteria needed to be met to be included in the study: 1) the surgeons explicitly diagnosed the patients with UIS in the electronic patient records; 2) wrist arthroscopy showed signs of type 2 lesions, such as triangular fibrocartilage complex (TFCC) degeneration and lunate chondropathy, according to Palmer; 19 3) magnetic resonance imaging (MRI) showed signs of focal abnormal signal intensity in the lunate, triquetrum, and ulnar head; 20 and 4) there was evident static or dynamic ulnar positive variance on standard posterior-anterior wrist radiographs in a neutral position. 21 This definition excluded three patients that underwent USO for other indications.…”
Section: Methodssupporting
confidence: 66%
“…The nonunion rate in our study sample was relatively high compared to our previous study (12% vs 6%) and the pooled estimate from the meta-analysis by Owens et al 40 (4%). 12 We could not find the cause for a higher incidence in our study as multiple prognostic factors for nonunion after USO, such as bone density and ROM, were not measured. 41 We observed that patients who experienced a nonunion (subsequently treated) had an impaired functional outcome at 12 months, but this difference disappeared at late follow-up.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…A case series involving 106 patients indicates that early long-arm plaster fixation can effectively reduce rotational stress on the fracture ends, promoting fracture healing. 84 This involves wearing a long-arm plaster for the first 2 weeks and a long-arm thermoplastic orthosis for the next 2 to 4 weeks, with wrist flexion/extension exercises starting from the 2nd week and forearm rotation exercises starting after the 6th week. Refixation was performed in six patients (6%) because of nonunion.…”
Section: Introductionmentioning
confidence: 99%